Uma proposta de intervenção com atividade física individualizada na deficiência intelectual: um estudo de caso - Panhan, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The practice of regular physical activity has been considered a protective factor against the degenerative processes of the body, acting as a promoter of health, especially for risk groups such as obese and resistant groups exercise adherence as among the intellectually disabled (ID) . This study involved the administration of a training protocol and the physical parameters of longitudinal health in a subject about 43 years, intellectually deficient, hypertensive, obese and with a strong predisposition to develop diabetes and heart disease. The main objective of long-term program was to reduce body weight and normalize blood pressure (BP) after the student's physical activity and preferentially interfere with BP values at rest (ie before the daily schedule). The other objective was to improve general physical fitness. The protocol involved four meetings per week lasting one hour, in addition to participation in the program PROEFA (twice a week with sessions of one hour each), totaling 57 sessions spread over five months. The evaluation protocol included in each session the following tests: blood pressure measurements and heart rate, and amount of physical activity recorded via pedometer. Tests applied before and after the training included: anthropometric assessment, agility test, flexibility test, test drive through vertical and horizontal jumps and endurance to the test bench. The mass (kg) and BMI corresponded to the initial values of 127.7 kg and 42.05 kg m-2, and 5 months after 113.2 kg and 37.48 kg m-2, respectively. The waist-hip ratio was close to 1 after the intervention and this value corresponded to 0.98. For the test of agility (shuttle run) was not found improvement in performance. To test the values of the horizontal jump in pre-test were 52 cm and 56 cm post-test, vertical jump has been improved and...(Complete abstract click electronic access below)

A prática regular de atividades físicas tem sido considerada fator de proteção contra os processos degenerativos do organismo, atuando como um agente promotor de saúde, especialmente para grupos de risco, como obesos, e grupos resistentes à aderência ao exercício, como ocorre entre os deficientes intelectuais (DI). O presente estudo envolveu a administração de um protocolo de treinamento físico e o acompanhamento longitudinal de parâmetros da saúde em um sujeito de 43 anos, deficiente intelectual, hipertenso, obeso e com forte pré-disposição para desenvolver diabetes ( níveis de glicemia maiores do que o desejável em jejum) e cardiopatias. O objetivo principal de longo prazo do programa foi reduzir a massa corporal e normalizar a pressão arterial (PA) do aluno depois da atividade física e, preferencialmente interferir nos valores da PA de repouso (ou seja, antes do programa diário). O outro objetivo foi melhorar a aptidão física geral. O protocolo envolveu quatro encontros por semana com duração de uma hora, além da participação no programa PROEFA (duas vezes por semana com sessões de uma hora cada), totalizando 57 sessões distribuídas em cinco meses. O protocolo de avaliação incluiu em cada sessão os seguintes testes: medidas de pressão arterial e frequência cardíaca, e quantidade de atividade física registrada via pedômetro. Testes aplicados antes e depois do treinamento incluíram: avaliação antropométrica, teste de agilidade, teste de flexibilidade, teste de impulso vertical e horizontal através de saltos e resistência aeróbia em teste de banco. A massa (Kg) e o IMC inicial corresponderam a valores de 127.7 Kg e 42.05 kg/m², e após 5 meses 113.2 Kg e 37.48 kg/m², respectivamente. A relação cintura quadril foi de 1,0075 e após intervenção este valor correspondeu a 0.98. Para...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Exercícios físicos; Deficientes mentais; Educação física para deficientes; Saude mental; Obesidade; Hipertensão; Execise; People with mental disabilities; Physical education and training; Mental health; Physical education for people with disabilities; Obesity; Hypertension